Factors contributing to job satisfaction among employees in Sarikei / Fadilla Hajar Abdul Manap and Irdina Maisarah Razshi - Abdul Manap, Fadilla Hajar; Razshi, Irdina Maisarah (2024)
The intention of this section is to give readers a better understanding of the research's background, including the research topic, research questions, and research objectives. This chapter as well set the scope of the research, explains the significance of this research, and provide the reader definitions to key terms in order to ensure the readers are able to understand the fundamental ideas behind this research.